Evaluation of Mucoadhesive Nano-Bilosomal In Situ Gels Containing Anti-Psychotic Clozapine for Treatment of Schizophrenia: In Vitro and In Vivo Studies - Marwa H. Abdallah; Mona M. Shahien; Hemat El-Sa; Enas Haridy Ahmed; Hanan M. El-Nahas; Nourhan A. Abdulla; Tarek M. Ibrahim (MDPI AG, 2024)
Background/Objectives: Patients with schizophrenia have significant challenges in adhering to and complying with oral medicines, resulting in adverse consequences such as symptom worsening and psychotic relapse. Methods: This study aimed to develop clove oil-based bilosomes using definitive screening design (DSD) to maximize the anti-schizophrenic action of clozapine and promote its nose-to-brain delivery. The target was to optimize the physicochemical properties of bilosomes and incorporate them into mucoadhesive intranasal in situ gels, searching for augmented ex vivo and in vivo clozapine delivery. Results: The bilosomes' particle size was decreased by increasing the span, SDC, and clove oil amounts. In addition to using a high lipid amount, the aforementioned components also helped increase the entrapment efficiency values. Increased zeta potential was only observed by increasing surfactant amount and reducing clozapine concentration. After incorporation of optimized liquid clove oil-based bilosomes, which had a spherical nano-sized vesicular shape, into P 407-dependent gels, an HPMC (2% w/w)/P 407 (20% w/w)-containing formulation (G6) was selected as an optimized gel owing to its acceptable gelation time (13.28 s), gel strength (27.72 s), viscosity (12,766.67 cP), and mucoadhesive strength (4273.93 dyne/cm2). The optimized G6 exhibited higher Jss (50.86 μg/cm2·h−1) through the nasal mucosa compared to the control gel (23.03 μg/cm2·h−1). Compared to the control gel, G6 displayed higher relative bioavailability (491.37%) than a commercial tablet (264.46%). Following ELISA analysis, dopamine and serotonin were significantly reduced, while BDNF was remarkably increased after administration of optimized G6 into schizophrenic rats. Conclusion: Our study indicates the potential of intranasal bilosomal gels in upgrading the anti-schizophrenic and neuroprotective activity of clozapine.